Workshop Digital Marketing dan Legalitas Usage Bagi Pelaku UMKM Desa Sumberagung - Arivatu Ni'mati Rahmatika; Bekti Widyaningsih; Imam Mawardi; Mada Restu Putri; Vicki Ade Irawan; Rois Hasyim; Winda Ayu Safitroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important part of the economy of a region or country. Based on the problems faced by MSME business actors, the aim is to provide additional insight to MSME actors in Sumberagung Village about the 7P marketing mix and the importance of business legality for MSMEs, in order to assist MSME businesses in expanding the marketing of their products in order to increase sales and income from the MSME business. The methodology in this research is the implementation of community service activities in the KKN-PPM program using the Community Based Research method, namely the resource person's explanation to partners. The method used in this activity is a meeting or face-to-face meeting between the resource person and partners located in Sumberagung Village, where the resource person plays an important role in explaining material regarding the 7P marketing mix and business legality for MSMEs. Based on observations, it can be seen that the problem is that many micro and small business owners do not understand the science of the marketing mix and business legality, which has an impact on the difficulty of expanding the marketing of their products. As a result, this affects the way they expand marketing and increase revenue from their products. MSMEs in Sumberagung Village need to be educated about the importance of the marketing mix, trained and assisted in obtaining NIB for marketing purposes, in order to expand markets and income. Apart from that, obtaining business legality and trademarks can help MSMEs become more competitive and competent in the markets.